Having Good Moral Values Through "Never Say Never" Song by Justin Bieber - Yuli Rohmiyati; Nazwa Sabrina Fatihah; Putri Solihatunnisa (Journal of linguistics, culture and communication, 2023)
The lyrics emphasize the importance of determination and having a positive mindset to overcome obstacles. This research paper analyzes the moral values present in the song "Never Say Never” by  Justin Bieber. The study aims to explore the moral values conveyed in the song lyrics. This research used a qualitative approach to analyze this song lyric. The data was analyzed by identifying, classifying, and interpreting the moral values. The findings of research found that three main moral values in the song: self-belief (57,14%), positivity (21,42%), and optimism (21,42%). The dominant moral value identified was self-belief, followed by positivity and optimism. These moral values can make students inspiring, provide them positive energy, and enable them to carry out worthwhile activities into education and personal development